Effect of carrying cell phones in trouser pockets, on semen parameters. - Munasinghe, D.A.L.; Weerasooriya, M.K.B.; Liyanage, J.A.; Wakkumbura, H.P. (Journal of International Research in Medical and Pharmaceutical Sciences, 2017)
A cross sectional study was carried out in the fertility clinic of the Gampaha Wickramarachchi Ayurveda Hospital (August 2014 to August 2015) to screen the effect of carrying mobile phones in trouser pockets on seminal parameters. Though, the mobile phones are an important instrument in the modern society, emitting of possible harmful rays is the disadvantage. However, the attention on the area is not sufficient. Thus, the current study was set up to fill the gap. In the study the male individuals who visited the clinic were evaluated to gather the data on usage of mobile phones. Then semen of each subject was collected and analyzed separately. Out of all (n = 76) 49 were used to carry the phones in trouser pocket sat least a while per day as a custom. However, when comparing the average semen parameters of them (test) such as semen volume, concentration, motility and morphology with the sameness of the non-users (control), a statistically insignificant reduction were seen in all parameters of the test group (P>0.05). Thus, the usage of mobile phone in trouser pockets has a lesser effect on the semen parameters. Perhaps, this could be due to the habit of subjects of non-continuous usage of the phones in pockets.
Keywords: trouser pocket; semen parameters; Mobile phone; male fertility